Low-Cost Retrofit Hybrid System For Myvi - Zafrullah, Muhammad Naseeruddin (Universiti Sains Malaysia, 2018)
Depletion of fossil fuel sources has become a concern to humankind as it is one of non-renewable energy that has been use over years. One of the alternative way to overcome the problem is the development of hybrid vehicles. Hydraulic Hybrid Vehicle (HHV) is one of the hybrid though it is uncommon compared to Hybrid Electric Vehicle (HEV), however the hydraulic hybrid technology has found its way to emerge itself into automotive industry. One of the configuration of hydraulic hybrid is parallel architecture, in which a conventional vehicle can be retrofitted into this architecture. The purpose of this project is to retrofit a conventional vehicle, Perodua Myvi 1.3L, with a hydraulic hybrid system with minimal cost. This is achieved by modification of the rear axle hub to placed hydraulic motor and pump on the rear axle of non-driven wheels. Upon retrofitting, a simulation of fuel economy on MATLAB is used to determine a suitable component sizing of hydraulic component and to determine the fuel economy improvement of the system.